2018
DOI: 10.1002/jqs.3004
|View full text |Cite
|
Sign up to set email alerts
|

Human response to habitat suitability during the Last Glacial Maximum in Western Europe

Abstract: This research takes a multi-dimensional approach to the study of the archaeological record of Western Europe during the Last Glacial Maximum (LGM), combining two distinct components of the human adaptive system (technological organization and mobility) to test the impact of environmental variability on the mobility of Upper Palaeolithic groups. To this end we make use of two models. The first predicts landscape suitability as a function of a suite of environmental variables including topography, climate and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Crombé, ), from the Middle Stone Age (Thompson et al, ) to the Mesolithic, and geographical contexts, from South Asia (Roberts et al, ) to Atlantic Iberia (i.e. Cascalheira and Bicho, ; Straus, ), sometimes bounded by great climatic phases, such as MIS 3 (Riel‐Salvatore and Negrino, ) or the Last Glacial Maximum (Burke et al ., ). Links between climate and human technological adaptations have been provided for large millennial scales to short Bond events.…”
Section: Discussionmentioning
confidence: 97%
“…Crombé, ), from the Middle Stone Age (Thompson et al, ) to the Mesolithic, and geographical contexts, from South Asia (Roberts et al, ) to Atlantic Iberia (i.e. Cascalheira and Bicho, ; Straus, ), sometimes bounded by great climatic phases, such as MIS 3 (Riel‐Salvatore and Negrino, ) or the Last Glacial Maximum (Burke et al ., ). Links between climate and human technological adaptations have been provided for large millennial scales to short Bond events.…”
Section: Discussionmentioning
confidence: 97%
“…The resulting model of habitat suitability was then used to design an agent-based model to test how habitat suitability structures patterns of human land use, population structure, connectivity, and patterns of gene flow (99) with implications for cultural reproduction that are still being explored. The implications of the habitat suitability model for the adoption of different human mobility strategies were then tested using the archaeological record and lithic retouch frequencies in a diachronic study (100). The results of this collaborative research program demonstrate the value of a multidisciplinary approach for each of the disciplines involved.…”
Section: The Archaeology Of Climate Changementioning
confidence: 99%
“…Reconstructing environmental conditions and climate change during the past, particularly at a seasonal resolution, is key for better understanding the impact of external changes on different aspects of human behavior [4,5,14]. Previous sclerochronological studies carried out on mollusks collected from northern Spain have revealed that δ 18 O shell values obtained from Phorcus lineatus [51,73], P. vulgata [74], P. depressa [72], and Mytilus galloprovincialis [83] can all be considered as effective high-resolution SST recorders.…”
Section: Sea Surface Temperature Reconstruction and Paleoclimate Implicationsmentioning
confidence: 99%
“…There has long been a keen theoretical and methodological interest in archaeology at elucidating the impacts of climatic and environmental change on hominin behavior, settlement, and culture in different parts of the world at different points of time [1][2][3][4][5], and how this might be mobilized to inform challenges facing our species in the 21st century [6,7]. In western Europe, climate changes have been variously argued to have had deep implications for Neanderthal behavior and eventual extinction [8][9][10], the tempo and nature of 2 of 17 human hunter-gatherer settlement across the Last Glacial Maximum and Early-Middle Holocene [11][12][13], and the arrival and adaptations of the first farmers [14,15].…”
Section: Introductionmentioning
confidence: 99%